Strategies to Improve Children's Ability to Recognize Shapes through Geometry Games - Sirjon, Sirjon; Setyaningsih, Diana; Handasah, Rr Retno; Solicha, Solicha (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Difficulty in recognizing geometric shapes in early childhood at YPPK Bintang Kecil Kindergarten, Abepura, Jayapura City, can hinder children's cognitive development and readiness for future mathematics learning. This study aims to improve children's ability to recognize, differentiate, and classify geometric shapes through a game-based learning approach. Involving 12 children aged 5–6 years, this study followed the Kemmis and McTaggart model for classroom action research, which was carried out for two cycles, each consisting of three actions. Data were collected through observation and testing, then analyzed using descriptive qualitative methods. The results showed a significant increase in children's shape recognition skills, with an average score increasing from 49.30% in the pre-cycle to 91.67% at the end of the second cycle. This increase was supported by the use of intriguing and concrete media, varied learning methods adjusted to children's learning styles, and the integration of games into learning activities. We conclude that the geometry game-based learning approach effectively enhances geometric shape recognition in early childhood. Further research is recommended to apply similar strategies in various educational settings and explore the use of digital educational games to further improve learning outcomes.